Pemahaman Kontekstual terhadap Al-Qur’an dan Hadist dalam Kehidupan Mahasiswa - Jimi Harianto; Shela Imelda; Marsha Aulia Azzahra (JIMAD: Jurnal Ilmiah Mutiara Pendidikan, 2026)
This study aims to explore the construction of students’ contextual understanding of the Qur’anic and Hadith texts and their relevance in addressing the challenges of modern life. The research is motivated by the persistence of a textual-normative learning paradigm in Islamic-based teacher education institutions, which risks creating a dichotomy between the authority of sacred texts and the dynamics of contemporary issues. Specifically, this study analyzes the development of critical and reflective thinking competencies among students of the PGSD Program at the private higher education institution STKIP Al Islam Tunas Bangsa in interpreting and actualizing the messages of the Qur’an and Hadith in relation to contemporary social issues. The method employed is Classroom Action Research conducted in two cycles, each consisting of the stages of planning, implementation of contextual learning actions, participant observation, and critical reflection. Data were collected through structured observations of classroom discussion dynamics, in-depth analysis of students’ reflective journals, and evaluation of case analysis projects, which were subsequently processed using thematic analysis. The findings reveal a significant transformation in students’ patterns of religious understanding, shifting from a literal approach toward analytical-contextual competence, as evidenced by their ability to relate religious textual messages to current issues such as digital media ethics, social justice, and environmental sustainability. The implications of this study underscore the urgent need to internalize a contextual approach within the Islamic Religious Education curriculum in private higher education institutions in order to build religious literacy that is applicable and adaptive to the changing times.